Taṣmīm Māddah al-Muḥādaṡah Bi Mauḍū al-Bīah al-Ma`hadiyah (Dirāsah al-Baḥṡ Wa at-Taṭwīr `An al-Qāmūs al-Ma`hadī Bi Ma`had Dār al-Iḥsān Abu Hasan Krueng Kalee-Aceh Besar) - Magdalena Magdalena; Zulhelmi Zulhelmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
This title was chosen by the writer because of the absence of particular books for the Arabic conversation of the student as well as an interview with the head of the language center of the school, Dr. Muakhir Zakaria MA. These questionnaires show that the students need certain guidance books used to improve their capability in Arabic conversation. The purpose of this study is to figure out the application of this material design and to measure the effectiveness of the design under the title “The environment of Islamic boarding school” to improve student’s abilities. The writer used the RND method and took the entire students of this boarding school as the population, while the sample is students from class 2D which is 30 students. Moreover, in data collection, the writer does observation, interviews, questions, and tests. The pre-test result of this test is 62% and the post-test 75% and it is more effective for them to use.